Synchronous Data Processing and Transmission System with Reference to the World Time Scale - H. G. Arzumanyan; H. A. Gomtsyan; O. J. Sevoyan (Известия высших учебных заведений России: Радиоэлектроника, 2016)
The methods of the high speed data processing and transmission systems, operating with large number of analog and digital sensors are investigated. Real time clock (RTC) device uses as system time generator for nonstop synchronous work. RTC is calibrated using the GPS signal for reference to the world time scale. In order to reduce the power consumption, the activation of the sensors occurs only at the survey and controlled by RTC.